28 Real-World Treatment Patterns, Healthcare Resource Utilization (HCRU) And Costs in First-Line (1L) Advanced Renal Cell Carcinoma (aRCC) in the US - Neil Shah; Ching-Yu Wang; Pratik Rane; Wei Gao; Esteban Lemus Wirtz; Tina Long; Julia Koloskova; Robert Motzer (The Oncologist, 2026)
Abstract Background Advances in tyrosine kinase inhibitor (TKI) and immuno-oncology (IO) therapies have reshaped the aRCC treatment landscape, necessitating an updated understanding of real-world treatment patterns, HCRU, and costs. Methods We conducted a retrospective cohort study using Optum’s deidentified Clinformatics® Data Mart Database (2019-2024). Adults with ≥2 claims with an RCC diagnosis, evidence of secondary metastasis, and who initiated first line (1L) systemic therapy (IO + IO, IO + TKI or TKI monotherapy) on or after April 19, 2019, were included. Treatment patterns, HCRU, and costs were examined. Overall survival (OS) was estimated using Kaplan-Meier method. Results Among 2,123 patients (mean age 68; 71% male), 82% received 1L IO-based therapy (IO + IO or IO + TKI), and 18% received 1L TKI monotherapy. Over 5 years, use of 1L IO+TKI therapies increased from 34% (2019) to 49% (2024), while TKI monotherapy use declined from 26% to 17%. During a median follow-up of 14 months, 686 (32%) patients remained on 1L therapy, 821 (39%) discontinued 1L (including 397 [19%] deaths) and 616 (29%) initiated second-line (2L), and 197 (9%) initiated third-line therapy. The median OS for the entire cohort was 35 months. Overall, 61% of patients had inpatient (IP) admissions (mean [median] length of stay: 2.7 [1.1] days), and 64% had emergency department (ED) visits (mean [median]: 0.4 [0.2] visits). Median total healthcare costs were $32,829 per-patient-per-month, including $21,630 medical costs and $10,770 pharmacy costs. Conclusions In this US claims population, we observed an increased adoption of 1L IO+TKI regimens with a decreasing trend of TKI monotherapy over time. While median OS has improved, reflecting improvements in the treatment and management of aRCC since 2019, there remain substantial HCRU and costs.